Theopreneurical Leadership: Konstruksi Model Pelayanan Pendeta-Pengusaha Berbasis Pendekatan Teologi Paulus - Tri Nugroho, Basuki (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
The problem of pastors who also work as entrepreneurs is a complex issue involving religious, social, and economic aspects. To overcome this problem, a comprehensive approach involving various related parties is needed and supported by clear regulations and strict law enforcement. Theological Entrepreneurship introduces the view that ministers of God can also be entrepreneurs, pursuing activities that involve business strategies to achieve more incredible spiritual and social outcomes. This provides a new perspective on the understanding of God's servants as agents of change who are competitive and able to adapt to the dynamics of modern society. The outline of this study is based on literature sources using the literature study method. Paul's influence in the church's history is evident in his travels and letters, which reflect a spirit of spiritual entrepreneurship. Through his work as a tentmaker or entrepreneur, Paul had more freedom to preach the gospel to the Jewish people. This shows how vital the "bridge of evangelism" is for a gospel preacher. Thus, the link between entrepreneurship and church ministry goes beyond just the concept of Christian ministry; it also includes various other aspects relevant to the church's purpose and vocation.